The influence of psycho-social factors on participation levels in community-based breast cancer prevention programs in Tehran, Iran - Ahmadian, Maryam; Abu Samah, Asnarulkhadi; Redzuan, Ma'rof; Emby, Zahid (Canadian Center of Science and Education, 2012)
Background: Although significant consideration has been devoted to women participation in breast cancer prevention programs, our understanding about the psychosocial factors which influence participation remains incomplete. Method: The study applied a quantitative approach based on the cross-sectional survey design and multistage cluster random sampling. A total of 400 women aged 35-69 years, were surveyed at 4 obstetric and gynecologic clinics affiliated to Tehran University of Medical Sciences in Tehran: the participation levels of 86 women who have had a mammogram were analyzed based on their self-efficacy, belief, social influence, and barriers concerning mammography utilization. Results: Consistent with the study framework, in bivariate analysis, the higher level of women’s participation in breast cancer prevention programs was significantly related to more positive belief about mammography (p< .05), greater social influence on mammography (p< .01) and fewer barriers to mammography (p< .01). Self efficacy (p= .114) was not significantly related to the higher level of participation. Conclusion: Results suggest that women’s participation levels in breast cancer prevention programs might be associated with the specific psychosocial factors on breast cancer preventive behavior such as mammography screening.